Application of refrigeration and packing can extend Butiá fruit shelf life. (August 2021) - Rockett, F.; Schmidt, H.; Rodrigues, E.; Flôres, S.; Rios, A.
Abstract: This research aimed to verify the shelf life of Butiá da Praia ( Butia catarinensis Noblick & Lorenzi) minimally processed, stored in packaging (with or without modified atmosphere) under conditions of refrigerated storage at 5 °C for 35 days. Physicochemical composition, bioactive compounds, and antioxidant capacity were analyzed. The fruit was stored at 5 °C in different treatments: arranged in expanded polystyrene trays; wrapped by multi-layer nylon-poly plastic packaging; and packed with 2% oxygen, 5% carbon dioxide, and 93% nitrogen. The fruit was evaluated for mass loss, pH, titratable acidity, soluble solids, firmness, moisture, color, and bioactive compounds such as carotenoids, ascorbic acid, and antioxidant capacity for 35 d. At 15 d, open treatment no longer had conditions of consumption. The use of packaging was able to increase softness; maintain carotenoid levels; maintain the antioxidant capacity of the fruit, and suffer less significant ascorbic acid losses. The use of packages combined with cooling (5 °C) was sufficient to prolong the shelf life for up to 25 d. Graphical abstract: Image 1 Highlights: A simple method to extend Butia catarinensis fruit shelf life was developed. At 15 d, open treatment no longer had conditions of consumption. Packages and cooling (5 °C), was sufficient to prolong the shelf life for 25 d. Packaging inscreased softness, maintained carotenoid levels and antioxidant capacity. Packed fruits suffered less significant ascorbic acid losses.